2020
DOI: 10.1177/0954408920916007
|View full text |Cite
|
Sign up to set email alerts
|

Numerical assessment of strain rate in an adhesive layer throughout double cantilever beam and end notch flexure tests

Abstract: The increasingly larger use of adhesive joints in the automotive industry demands a full comprehension of the adhesive behaviour when subjected to dynamic loadings. So far, some authors studied the effect of the strain rate regarding the adhesives performance, usually for the range of approximately 0–105/s; nevertheless, few studies are clear regarding the method used to calculate strain rate, especially when fracture mechanics analysis is the focus of study. Those who present approaches to assess the values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…These results are compared with simulations of the strain rate evolution for the same adhesives at constant velocities of 150 and 15 mm/s, some of which were performed in a previous work. 19 For all the cases shown, it is possible to notice that the values of strain rate are pretty much constant throughout the tests. The biggest deviation, around 20% of the target value, was found for the case of the Nagase XNR6852 E-3 at constant strain rate of 100 s -1 .…”
Section: Numerical Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…These results are compared with simulations of the strain rate evolution for the same adhesives at constant velocities of 150 and 15 mm/s, some of which were performed in a previous work. 19 For all the cases shown, it is possible to notice that the values of strain rate are pretty much constant throughout the tests. The biggest deviation, around 20% of the target value, was found for the case of the Nagase XNR6852 E-3 at constant strain rate of 100 s -1 .…”
Section: Numerical Resultsmentioning
confidence: 85%
“…As mentioned before, the authors first assessed how the strain rate changed as the crack propagates along the specimens of DCB and ENF tests in a previous study. 19 One of the main conclusions of that study was that the variation of strain rate could be significant for the determination of the energy release rate in mode I, since it was found that the strain rate in the final part of the test was around three times lower than that measured at the beginning of the test.…”
Section: Determination Of Control Curve To Perform Dcb Tests At Constant Strain Ratementioning
confidence: 89%
See 2 more Smart Citations
“…Nunes et al. 11 studied the influence of strain rate on modes I and II fracture energy. Their results showed that when a DCB specimen is loaded at a constant cross-head speed, the strain rate is not constant ahead of crack tip.…”
Section: Introductionmentioning
confidence: 99%